Digital citizenship for sustainable development goals: A character-based approach in civic education - Suriadi Ardiansyah; Anthony Anggrawan; Dadang Iskandar (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
This paper explores the transformative role of character-based digital citizenship in redefining civic education in the digital era. Amid the rapid flow of information and the growing negative impact of technology on national values, civic education must be adaptive and relevant. The study highlights the strategic contribution of digital citizenship to achieving the Sustainable Development Goals, in particular Target 4.7, which emphasises education for sustainable development and global citizenship, and Target 16, which supports peaceful and inclusive societies and access to justice. This research applies a descriptive qualitative approach, using a systematic literature review strategy combined with thematic analysis, to critically and in-depth explore relevant scientific literature. These findings suggest that integrating character education into digital citizenship fosters ethical awareness, responsible digital behaviour, and democratic participation. This synergy strengthens civic competence and promotes inclusive, peaceful, and sustainable educational settings. The study provides strategic insights for educators, curriculum developers, and policymakers, proposing new conceptual models that align digital citizenship with global citizenship goals and advance 21st-century citizenship learning.